Challenges in Protecting Trafficking Victims' Rights in Indonesia: Tantangan dalam Melindungi Hak-Hak Korban Perdagangan Orang di Indonesia - Hidayat, Muchammad Eko; Effendi, Tolib (Rechtsidee, 2023)
This research focuses on the critical analysis of legal frameworks in Indonesia concerning the protection of witnesses and victims in human trafficking cases, scrutinizing the effectiveness and challenges from a perspective of dignified justice. Emphasizing the need for a fair judiciary system, the study delves into the implementation of existing laws and regulations related to the rights and protection of witnesses and victims in Trafficking in Persons (TPP) cases. Employing a normative legal methodology, the research extensively analyzes national and international norms and legal materials, including comparisons between national laws and international conventions such as the Palermo Protocol. Findings reveal that inadequate understanding and awareness among law enforcement about the significance of these rights, coupled with resource constraints, result in identity rights violations for witnesses and victims. Furthermore, challenges such as the perceived threats to witnesses and victims, limited human and financial resources in law enforcement agencies, legal uncertainties in TPP case handling, insufficient international cooperation in law enforcement, and the difficulty in balancing the rights of victims and defendants are identified. The study also highlights the importance of rehabilitation and reintegration policies for victims, suggesting that successful combat against human trafficking transcends judicial processes. Consequently, this research not only investigates existing laws and policies but also identifies gaps and potential improvements to ensure that witness and victim protection in combating TPP aligns with principles of dignified justice. The aim is to contribute significantly to developing a more effective, fair, and rights-sensitive judicial system in Indonesia. Highlights: Law Enforcement Gaps: Limited awareness and resources in protecting victims' rights. Legal and International Hurdles: Challenges in TPP case handling and cross-border cooperation. Rights Balance: Need for equilibrium between victim protection and defendant fairness. Keywords: Human Trafficking, Witness Protection, Legal Framework, Indonesia, Rights of Victims